2019
DOI: 10.1016/j.stemcr.2019.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Autologous, Gene-Modified Hematopoietic Stem and Progenitor Cells Repopulate the Central Nervous System with Distinct Clonal Variants

Abstract: Summary Myeloid-differentiated hematopoietic stem cells (HSCs) have contributed to a number of novel treatment approaches for lysosomal storage diseases of the central nervous system (CNS), and may also be applied to patients infected with HIV. We quantified hematopoietic stem and progenitor cell (HSPC) trafficking to 20 tissues including lymph nodes, spleen, liver, gastrointestinal tract, CNS, and reproductive tissues. We observed efficient marking of multiple macrophage subsets, including CNS-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
9
8
0
Order By: Relevance
“…In the cerebellum, CAR staining frequencies were below the threshold in all 4 macaques, indicating minimal to no trafficking of gene-modified cells to this site. In agreement with our previous studies, these findings strongly suggest that HSC-derived progeny engraft and persist long-term in the brain ( 43 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In the cerebellum, CAR staining frequencies were below the threshold in all 4 macaques, indicating minimal to no trafficking of gene-modified cells to this site. In agreement with our previous studies, these findings strongly suggest that HSC-derived progeny engraft and persist long-term in the brain ( 43 ).…”
Section: Resultssupporting
confidence: 93%
“…Therefore, the HSC-derived CD4CAR + cell types we observed in the CNS remain to be fully characterized. Nevertheless, our findings in the CNS are consistent with previous studies from our group and others ( 43 , 64 ), demonstrating that HSC-derived therapies enable trafficking of cell-based therapies to the brain, and in close proximity to potential CNS-associated viral reservoirs ( 65 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also observed that HSPC-derived MLCs were durably engrafted within the brain over a year post-transplantation and that these cells bore many of the transcriptional hallmarks of microglia, which strongly suggest they have the capacity to selfrenew much like endogenous microglia. This is consistent with long-term follow-up of HSPC-GT in nonhuman primates, where HSPC-derived myeloid cells in the brain were observed ten years posttransplantation 15 . It is similarly consistent with the durable phenotypic rescue in most patients enrolled in clinical trials for MLD and CALD 48 .…”
Section: Discussionsupporting
confidence: 88%
“…2h). Of note, we observed a general lack of correlation of biodistribution metrics (VCN, mRNA, protein) in peripheral tissues versus brain, consistent with previous clinical and preclinical reports 15,20,29 that engraftment in these two compartments are independent events that occur from separate cell populations derived from the drug product (Supp. Fig.…”
Section: Intravenous (Iv) and Intracerebroventricular (Icv) Administration Both Show Engraftment In The Brain But Only IV Shows Engraftmesupporting
confidence: 89%